2015
DOI: 10.14245/kjs.2015.12.3.153
|View full text |Cite
|
Sign up to set email alerts
|

An Incidental Finding of a Radiopaque Pill following Cervical Spinal Surgery in a Parkinson's Disease Patient

Abstract: There are previous reports of the identification of radiopaque medications on abdominal X-rays or computed tomography (CT). We describe an interesting case of the incidental identification of a radiopaque medication on cervical spinal CT following cervical spinal surgery. A sixty seven-year-old male patient with Parkinson's disease (PD) visited our emergency center with a C5-6 dislocation and fracture. Surgery was performed with open reduction and pedicle screw fixation through the posterior approach. No abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In previous studies, the efficacy and safety of cervical pedicle screw (CPS) placement has been shown, even with a freehand technique. 47) The authors have also shown the effectiveness of CPS placement in traumatic conditions, especially subaxial cervical spine facet dislocation. 8,9) In this study, two challenging but successfully treated cases of cervical spondyloptosis, C7–T1 level, were described in which the dislocation was completely reduced and the short segment was fused using CPS placement and interbody grafting through a posterior approach.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the efficacy and safety of cervical pedicle screw (CPS) placement has been shown, even with a freehand technique. 47) The authors have also shown the effectiveness of CPS placement in traumatic conditions, especially subaxial cervical spine facet dislocation. 8,9) In this study, two challenging but successfully treated cases of cervical spondyloptosis, C7–T1 level, were described in which the dislocation was completely reduced and the short segment was fused using CPS placement and interbody grafting through a posterior approach.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated the effectiveness and safety of CPS placement even in patients with degenerative cervical spinal pathology such as parallel-shaped cervical FS 5,9,17,20,21,[25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated the effectiveness and safety of CPS placement even in patients with degenerative cervical spinal pathology such as parallel-shaped cervical FS [ 5 , 9 , 17 , 20 , 21 , 25 - 27 ]. Here we compared ACDF with uncinate removal and PCF with wide facetectomy in the treatment of parallel-shaped severe bony cervical FS.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed the efficacy and safety of placing a large series of cervical pedicle screws (CPSs) in patients with severe pathology of the cervical spine. 3 6 12 15 16 17 19 20 21 24) To date, there are no reports regarding the treatment of severe cervical FS by PF using FPS. In this study, we demonstrate the efficacy and safety of posterior facetectomy with fusion using pedicle screw (PF using FPS) to treat parallel-shaped severe cervical FS.…”
Section: Introductionmentioning
confidence: 99%